Exploring the world hot springs: A bibliometric analysis of global trends in metagenomics research - Atif Khurshid Wani; Tahir ul Gani Mir; Nahid Akhtar; Chirag Chopra; Juliana Heloisa Pinê Américo-Pinheiro; Munleef Quadir; Krishna Kumar Yadav; Pankaj Kumar; IGAA Indrayani; Amik Krismawati; Anik Herwati; Reena Singh (Current Research in Biotechnology, 2023)
The aim of the present study is to utilize bibliometric analytical tools to examine the trends in research publications within the hot spring metagenomics field. To achieve this, an in-depth exploration of the Scopus and Web of Science (WoS) databases was undertaken to recognize scholarly articles within this research domain that were published from 2005 to 2022. As a result, a dataset consisting of 377 articles was obtained. The VOSviewer, RStudio, MS Excel, and MS Access were utilized to investigate the annual publication trend, the most productive journals, organizations/authors/countries, authorship and citation patterns, the most cited documents/articles, and the co-occurrence of keywords. According to the findings, the initial article related to hot spring metagenomics was published in 2005. At the end of 2010, the number of published articles was merely 27. However, since then, there has been a significant rise in the yearly number of publications, and post-2010, more than 20 articles have been published every year. The countries with the highest publication output in the field of hot spring metagenomics from 2005 to 2022 were the United States, India, China, and Japan. Montana State university, University of Nevada, Pennsylvania State University, and Bigelow laboratory for ocean sciences all from US have been most active organizations working in this field. The authors who have the highest number of citations, with Ward M. having 1202 and Bryant A. having 1173, also have the greatest total link strength (TLS) of 643 and 653, respectively. Around 11.40 % of the articles published across various sources and journals were contributed by Frontiers in Microbiology, which had the highest number of publications. Bryant's research article, published in 2007 in the Science journal, about phototrophic microbial mats in alkaline siliceous hot springs, has the highest citation score of 292 as of 2022. This research provides a comprehensive overview of the research landscape in hot spring metagenomics and to identify research trends, patterns, and knowledge gaps in this field. This information could be used by researchers, policymakers, and other stakeholders to make informed decisions about future research directions and priorities in hot spring metagenomics.